PEMODELAN ARUS PASANG SURUT DAN SEDIMEN MELAYANG DI MUARA SUNGAI BELAWAN - Dhika Swandana (Jurnal Teknik Sipil USU, 2017)
ABSTRACT Belawan River estuary is a potential estuary with the strategic location, derives it as a port location and local economy growth sector as well as international. However, the issue of climate chaging and unbalanced exploration bring many problems toward the components of estuary. Tidal flood, seawater intrusion, and sedimentation are some of those problems. The purpose of the research is to know the situation and characteristic of Belawan River estuary. The components of estuary, such as: bathymetry, current, tidal, temperature, salinity, and sediment are analyzed based on laboratoriun test and  survey. And then being analyzed with literature and created to be a model in particular computer programming. The score of the components are connected and presented with the certain observation and time. Bathymetry is calculated with exponential equation, tidal flow are visualized in sine function, temperature and salinity and then calculated with Gauss distribution, and obtained sediment levelfrom the accumulation of erosion factor. From the research, we can be conclusion that tidal raising is affecting the Belawan River estuary’s characteristic as far as 18 km from the estuary mouth. The water depth which is affected by the main components ofsolar semidiurnal (S2) , lunar semidiurnal (M2), and lunar quarter diurnal (M4) create a maximum tidal difference with 1,9 metre high. The estuary is not only affected by seawater, but also the riverwater discharge which causethe water molecul displacement from upstream to the sea and vice versa. This case creates the score of temperature, salinity, and sediment level becomes nonlinear at its point and hour. Also it can be goined the maximum sediment scorewith 373.69 mg/dm3. Key words: estuary, bathymetry, current, tidal, temperature, salinity, sediment